O Protagonismo feminino nas práticas espaciais da Associação Indígena Borari de Alter do Chão- AIBAC - Santarém/PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The objective of the research is to present an analysis of the spatial practices of the Borari (the word Borari that gives its name to the festival, means “poisoned arrow”) Indigenous Association of Alter do Chão (AIBAC), with focus on female protagonism. The association was founded in Alter do Chão on the twenty-ninth of January 2008. It was created to fight and defend the rights of the Borari indigenous people in public and private institutions. The association is a non-profit and indefinite entity. The native peoples of Brazil and the world live in a scenario of violation of their rights, between invasion of their territories, denial of their identities and absence of differentiated politics by the State, which is not very different from Borari territory. The AIBAC since its foundation has been providing gains in autonomy for the Borari indigenous people of Alter do Chão, mainly related to the recognition and demarcation of their indigenous territory with FUNAI. The participation of indigenous women in the Borari territory has assumed an important front in the struggle to guarantee women's rights and autonomy, in the protection of nature and demarcation of the territory. The spatial practices carried out by AIBAC focus on social and cultural actions. In both social and cultural projects, spatial practices aim at the alternative economic circuit and location through the strength of the identity of the Borari people. The indigenous Borari always had women in their command, being a village of matriarchal origin, today who is in command is the cacique Ludinéia Lobato Gonçalves Dias, together with other Borari indigenous women created the in Association Borari indigenous the Women's Nucleus denominated Sapú Borari, demonstrating indigenous female empowerment. The spatial practices that take place at AIBAC are mainly promoted by the women’s Nucleus Sapú Borari, actions and projects; however, the struggle for rights is aimed at the entire Borari indigenous people, not just these women. Through my research my hypothesis was confirmed that the Borari matriarchal organization has repercussions on spatial practices and would probably be different if the Borari patriarchal organization.
Keywords: AIBAC.; mulheres indígenas Borari; Núcleo de mulheres Sapu Borari; Matriarcado; CNPQ:: CIÊNCIAS HUMANAS